Real-world solutions for developing high-quality PHP frameworks and applications - Bergmann, Sebastian, 1978-; Priebsch, Stefan; Safari eBooks (Indianapolis, IN : Wiley Pub., 2011)
Presents information and a variety of case studies focusing on creating sustainable applications and frameworks using PHP.
Description based on print version record.
Includes bibliographical references and index.
Keywords: PHP (Computer program language); Application software -- Development; Web sites -- Design; Electronic books